PTEN expression in endothelial cells is down-regulated by uPAR to promote angiogenesis - Unseld, Matthias; Chilla, Anastasia; Pausz, Clemens; Mawas, Rula; Breuss, Johannes; Zielinski, Christoph; Schabbauer, Gernot; Prager, Gerald W. (Thrombosis and Haemostasis, 2015)
The tumour suppressor phosphatase and tensin homologue (PTEN), mutated or lost in many human cancers, is a major regulator of angiogenesis. However, the cellular mechanism of PTEN regulation in endothelial cells so far remains elusive. Here, we characterise the urokinase receptor (uPAR, CD87) and its tumour-derived soluble form, suPAR, as a key molecule of regulating PTEN in endothelial cells. We observed uPAR-deficient endothelial cells to express enhanced PTEN mRNA- and protein levels. Consistently, uPAR expression in endogenous negative uPAR cells, down-regulated PTEN and activated the PI3K/Akt pathway. Additionally, we found that integrin adhesion receptors act as trans-membrane signaling partners for uPAR to repress PTEN transcription in a NF-κB-dependent manner. Functional in vitro assays with endothelial cells, derived from uPAR-deficient and PTEN heterozygous crossbred mice, demonstrated the impact of uPAR- dependent PTEN regulation on cell motility and survival. In an in vivo murine angiogenesis model uPAR-deficient PTEN heterozygous animals increased the impaired angiogenic phenotype of uPAR knockout mice and were able to reverse the high invasive potential of PTEN heterozygots. Our data provide first evidence that endogenous as well as exogenous soluble uPAR down-regulated PTEN in endothelial cells to support angiogenesis. The uPAR-induced PTEN regulation might represent a novel target for drug interference, and may lead to the development of new therapeutic strategies in anti-angiogenic treatment.
Keywords: Angiogenesis; endothelial cell behaviour; PTEN; urokinase receptor